Expressed disapproval does not sustain long-term cooperation as effectively as costly punishment - Adam Sparks; Tyler Burleigh; Pat Barclay (Evolutionary Human Sciences)
Punishment plays a role in human cooperation, but it is costly. Prior research shows that people are more cooperative when they expect to receive negative feedback for non-cooperation, even in the absence of costly punishment, which would have interesting implications for theory and applications. However, based on theories of habituation and cue-based learning, we propose that people will learn to ignore expressions of disapproval that are not clearly associated with material costs or benefits. To test this hypothesis, we conducted a between-subjects, 40-round public goods game (i.e. much longer than most studies), where participants could respond to others’ contributions by sending numerical disapproval messages, paying to reduce others’ earnings, or neither. Consistent with previous results, we observed steadily increasing contributions in the costly punishment condition. In contrast, contributions declined after the early rounds in the expressed disapproval condition, and were eventually no higher than the basic control condition with neither costly punishment nor disapproval ratings. In other words, costless disapproval may temporarily increase cooperation, but the effects fade. We discuss the theoretical and applied implications of our findings, including the unexpectedly high levels of cooperation in a second control condition.